In front of the children : screen entertainment and young audiences (London : British Film Institute, 1995)
There is no shortage of opinion about how the media affect children, but surprisingly little evidence about what children themselves choose to watch, or about the production and marketing choices made on children's behalf.
Keywords: Psychology; Children; Television; Child psychology; Television and children; Motion pictures and children